The Basic Concept of Proceedings in Religious Courts: Sharia Perspectives and Positive Law - Batul, Fatimatuz Zahroil (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2025)
This research examines the fundamental concepts of legal proceedings in Indonesian religious courts through the perspectives of sharia and positive law. The main issue studied is how to harmonize these two legal systems in religious court practice. The research method uses a normative juridical approach with comparative analysis of Islamic legal sources and Indonesian legislation. The research findings show that the concept of legal proceedings from a sharia perspective is based on the principles of justice (‘adl), transparency (syafāfiyyah), and public interest (maṣlaḥah) sourced from the Qur’an and Hadith. Meanwhile, Indonesian positive law applies the principles of contradictory proceedings, publicity, and dispositional nature sourced from Herziene Indonesisch Reglement (HIR) and the Rechtsreglement voor de Buitengewesten (RBg). Although there are similarities in the principles of justice and evidence procedures, fundamental differences are found in legal sources, philosophical approaches, and procedural flexibility. Harmonization is achieved through the adoption of peace principles (islah) and sharia evidence systems within the civil procedural law framework. This research recommends the need for reformulation of religious court procedural law that integrates sharia values with the national legal system to achieve legal certainty and substantive justice.